Joint Impact Assessment of CTA's Support to AFRACA (2004-2014) - Amimo, John; Gichuhi, Daniel; Chelule, Cheryl (Technical Centre for Agricultural and Rural Cooperation, 2020)
The partnership between CTA and AFRACA dates back to more than 10 years ago. During that time, CTA supported AFRACA undertake several activities, with the bulk of the support going to logistical support covering participants’ transport and subsistence for seminars, workshops, meetings and learning tours.